Factors Affecting EFL Preservice Teachers’ Self-Efficiacy - Zain, Dodi S. M.; Syajara, Amelia (UIR Press, 2025)
Teachers’ self-efficacy is considered an important teaching element that determines the success of teaching. However, self-efficacy is dynamic and depends on various factors. This study investigates the factors that influence preservice teachers’ self-efficacy in teaching. It further describes preservice teachers’ efforts to develop self-efficacy. Adopting a phenomenological approach, the study used interviews as the main instrument for the data collection. A total of eight participants of Indonesian EFL preservice teachers were recruited using purposive sampling. Using thematic analysis, this study formulated five themes: (1) learning experience, (2) teaching anxiety, (3) teaching support, (4) teaching quality, and (5) self-management. The study concluded that both positive and negative learning experiences affect preservice teachers' self-efficacy. Teaching anxiety, which derives from such variables as parental interference, learning engagement, and academic burden, also serves as another influential factor of self-efficacy. Lastly, EFL preservice teachers’ efforts to develop self-efficacy include improving teaching competence and skills, practicing self-management skills, and gaining support from families, friends, and institutions. This study formulates several implications, including the need for more intensive programs to better prepare EFL preservice teachers in their teaching practicum and the urge for universities to provide meaningful learning experiences.